Pengaruh Kompos Jerami Dan Pupuk NPK Terhadap N-Tersedia Tanah, Serapan-N, Pertumbuhan, Dan Hasil Padi Sawah (Oryza sativa L) - Elizabet Kaya (Agrologia, 2013)
Nitrogen is a major nutrient for plant growth, nitrogen was absorbed by plant roots in the form of NO3-(nitrate) and NH4+ (ammonium). Nitrogen deficiency affects negatively on plants, like stunted plant, leaf turns yellow, and limited rooting system, while excess nitrogen causes elongated vegetative growth, easy to fall down, reduce the grain quality and its response to pests and diseases. The purpose of this study is to determine the available soil-N, plant N uptake and growth as well as the yield of paddy rice (Oryza sativa L) due to the treatment of straw compost and NPK fertilizer. Treatment was carried out in a factorial experiment designed in randomized block design, the straw compost factor consisted of  two dose levels: 0 and 3.0 ton ha-1 and NPK fertilizer factor consisted of five dose levels: 0, 75, 150, 225, and 300 kg ha-1 with three replications. Research findings indicated that the amendment of straw compost together with NPK fertilizer increased the plant uptake of N, but straw compost improved independently the soil-N, and plant growth (plant height and number of tillers/clump). Likewise, NPK fertilizer independently increased soil-N, growth parameter (plant height and number of tillers/clump) and grain yield (number of grains/panicle and number of filled grain/panicle). The straw compost amendment at 3 tons ha-1 along with 150 kg NPK ha-1 resulted the highest N-uptake of 3.51%.